Job applications : the winning edge - Shmerling, Leah. (South Melbourne, Vic. : Macmillan Education, 1988)
This book is about: Job-planning and employment skills; Job applications methods; Business letter writing; ...
Keywords: Letter writing; Applications; Letter writing; Applications for positions